2020
DOI: 10.1111/hsc.13148
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods systematic review of informal caregivers' experiences of fall risk among community‐dwelling elders with dementia

Abstract: Evidence on effective fall prevention strategies for community‐dwelling elders with dementia is limited, although these elders are at high risk of falling. Informal caregivers may play an essential role in managing fall risk for elders with dementia. Thus, understanding caregiver's experiences is critically important. This systematic review aims to (a) identify caregivers' perceptual, emotional and behavioural responses to fall risk in elders with dementia and (b) examine the outcomes and effects of caregiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…On the one hand, the limitation of physical capacity reduced their energy to participate in PA (Cedervall et al, 2015). On the other hand, as the interviews with caregivers indicated, their limited reduced physical capacity reduced opportunities for the patients to take part in outdoor activities alone, because of anxiety about them falling (Malthouse & Fox, 2014;Zhou et al, 2020). In line with "COM-B system," capacity and opportunity were key factors for participation in PA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, the limitation of physical capacity reduced their energy to participate in PA (Cedervall et al, 2015). On the other hand, as the interviews with caregivers indicated, their limited reduced physical capacity reduced opportunities for the patients to take part in outdoor activities alone, because of anxiety about them falling (Malthouse & Fox, 2014;Zhou et al, 2020). In line with "COM-B system," capacity and opportunity were key factors for participation in PA.…”
Section: Discussionmentioning
confidence: 99%
“…The neuropsychiatric symptoms were mainly expressed as emotion (e.g., apathy) and behavioral problems (e.g., psychomotor alterations) in this survey (Table 2). These symptoms are not only associated with negative thought processes to engage in activities (Rist et al, 2015), but also are the leading causes of disturbance in normality of the ADL and augment the caregivers' worries about their falling (Urwyler et al, 2017;Zhou et al, 2020). The continuity and regularity of daily life are convenient for the arrangement of PA based on the patients' physical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that supporting care partners to manage fall risk might be effective in reducing this risk for community-dwelling OLWD [ 14 ]. A recent systematic review found that care partners adopted multi-level (individual, interpersonal, physical environment, and community/institutional level) strategies to manage fall risk for OLWD that they cared for; however, these review findings were based on studies that were not designed to systematically examine care partners’ experiences of fall risk management (FRM) [ 15 ]. Available tools and interventions developed to support or involve care partners in managing fall risk for OLWD included a decision-making discussion tool for the falls prevention [ 16 ], a Home Safety Toolkit [ 17 ], and a dyadic Tai Chi exercise program [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Primary care partners tend to provide practically round-the-clock care, including OLWD’s activities of daily living, mobility, instrumental activities of daily living, and overall health management; secondary care partners often provide supplementary support to OLWD, especially supporting OLWD’s basic daily tasks [ 22 25 ]. However, previous studies have not described how care partners’ FRM behaviours differ by their caring responsibilities [ 15 ], which might not give a complete picture of FRM in the context of dementia caregiving.…”
Section: Introductionmentioning
confidence: 99%
“…His scheme is in psychological approach, to prevent elders from falling is from the framework of managing fear of falling. Y Zhou, et al [3] Published a paper in 2020.…”
Section: Introductionmentioning
confidence: 99%